2020
DOI: 10.1016/j.msea.2019.138679
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electropulsing on the fatigue resistance of aluminium alloy 2014-T6

Abstract: The effects of electropulsing on the fatigue resistance of aluminium alloy 2014-T6 were studied in relation to electric current amplitude, pulse duration, and number of repetitions. Utilising the Taguchi method, the present study identified the current amplitude and the duration of the electropulsing as the two critical treatment parameters for improved fatigue resistance. A 97% fatigue life improvement was achieved under the electropulsing conditions that were applied. An increase in microhardness and a decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In the last 40 years, there has been growing interest in the use of external magnetic fields to improve materials properties. Studies have shown that an external magnetic field can improve fatigue resistance [14,15], microhardness [16], corrosion resistance [17] and tribological properties [18,19]. There is also evidence that the application of a magnetic field may lead to stress relief and stress relaxation [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In the last 40 years, there has been growing interest in the use of external magnetic fields to improve materials properties. Studies have shown that an external magnetic field can improve fatigue resistance [14,15], microhardness [16], corrosion resistance [17] and tribological properties [18,19]. There is also evidence that the application of a magnetic field may lead to stress relief and stress relaxation [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Noell et al found that electropulsing can be used to modify the microstructures of additive manufacturing metals such as 316 l stainless steel and AlSi10Mg [9]. Babutskyi et al studied the effects of electropulsing on the fatigue resistance of 2014-T6 aluminum alloy by means of scanning electron microscopy and transmission electron microscopy experiment [10]. In terms of coupled electropulsing energy simulations, Ren et al [11] used ANSYS to simulate the microcrack healing process of TC4 under the effect of the pulsed electric field.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 40 years, there has been growing interest in the use of external magnetic fields to improve materials properties. Studies have shown that an external magnetic field can improve fatigue resistance [14,15], microhardness [16], corrosion resistance [17] and tribological properties [18,19]. There is also evidence that the application of a magnetic field may lead to stress relief and stress relaxation [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that the application of a magnetic field may lead to stress relief and stress relaxation [20,21]. These improvements in materials properties have been attributed to a variety of factors including changes in the dislocation density [22,23], grain refinement [24] and the generation of precipitates [14]. Research conducted by Bockstedt et al [25] has shown that pulsed magnetic field treatment can lead to changes in the hardness and in the state of residual stresses in materials, while another study by Bataineh et al [26] has reported the benefits of reducing the wear of cutting tools.…”
Section: Introductionmentioning
confidence: 99%